Factors influence guests’ satisfaction to continually accommodate at Hatten Hotel / Nurul Farhana Abd Majid - Abd Majid, Nurul Farhana (2014)
The purpose of this study is to identify the factor influence guests’ satisfaction. The research is based on a sample of 93 respondents who accommodate and had spent their nights at Hatten hotel at least for one night. The results show that cleanliness, facilities, safety, location and price have significant relationship with guests’ satisfaction. However, only facilities and price have significant influence towards the satisfaction level of the guests. While location, cleanliness and safety are not statistically significant in influencing guests’ satisfaction.